2008
DOI: 10.1242/jeb.008755
|View full text |Cite
|
Sign up to set email alerts
|

Production of different phenotypes from the same genotype in the same environment by developmental variation

Abstract: SUMMARY The phenotype of an organism is determined by the genes, the environment and stochastic developmental events. Although recognized as a basic biological principle influencing life history, susceptibility to diseases, and probably evolution, developmental variation (DV) has been only poorly investigated due to the lack of a suitable model organism. This obstacle could be overcome by using the recently detected, robust and highly fecund parthenogenetic marbled crayfish as an experimental an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
184
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(194 citation statements)
references
References 52 publications
5
184
0
4
Order By: Relevance
“…However, there is also variation in the behavioural outcomes of development among otherwise rather similar individuals, such as littermates, that are brought about by differential accommodation to the disruptions of normal development. The strength of such developmental variability has been revealed by a remarkable study of clonal crayfish raised under identical environmental conditions [137], but it remains poorly studied among mammals. Epigenetic modifications of genetic information can also result in modulation of offspring social behaviour in response to social or ecological stimuli during early development [138,139], highlighting the fact that genetic and developmental mechanisms are inseparable and may often be closely linked to social and ecological ones.…”
Section: (B) Developmental Constraintsmentioning
confidence: 99%
“…However, there is also variation in the behavioural outcomes of development among otherwise rather similar individuals, such as littermates, that are brought about by differential accommodation to the disruptions of normal development. The strength of such developmental variability has been revealed by a remarkable study of clonal crayfish raised under identical environmental conditions [137], but it remains poorly studied among mammals. Epigenetic modifications of genetic information can also result in modulation of offspring social behaviour in response to social or ecological stimuli during early development [138,139], highlighting the fact that genetic and developmental mechanisms are inseparable and may often be closely linked to social and ecological ones.…”
Section: (B) Developmental Constraintsmentioning
confidence: 99%
“…The phenotype of an organism is determined by the genes, the environment and by stochastic developmental events (Vogt et al, 2008). Vogt et al (2008) stated that, even in the same environment, individual genotypes can produce different phenotypes because of developmental variation, resulted in generating variability among clone-mates and individuality in a parthenogenetic species.…”
Section: Chemical Factorsmentioning
confidence: 99%
“…Vogt et al (2008) stated that, even in the same environment, individual genotypes can produce different phenotypes because of developmental variation, resulted in generating variability among clone-mates and individuality in a parthenogenetic species. This developmental variation, an apparently ubiquitous phenomenon in living beings, can introduce elements of randomness into life histories, altering individual fitness and subsequently population dynamics.…”
Section: Chemical Factorsmentioning
confidence: 99%
“…Its closest relatives seem to belong to the genus Procambarus (Scholtz et al 2003). Unpublished molecular analyses of its mitochondrial genome suggest it to be a parthenogentic strain of the North American cambarid Procambarus alleni (Keith Crandall, unpublished data as cited in Vogt et al 2008). This organism is an outstanding crustacean because it provides the first example for parthenogenesis within the decapod crustaceans (Scholtz et al 2003;Seitz et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This organism is an outstanding crustacean because it provides the first example for parthenogenesis within the decapod crustaceans (Scholtz et al 2003;Seitz et al 2005). Most recently, it has been shown that the Marbled Crayfish reproduces by apomictic parthenogenesis, the most common asexual reproductive mode among invertebrates (Martin et al 2007;Vogt et al 2008). By apomictic propagation, the offspring conserve the original genetic information and, thus, are identical clones of the mother (Martin et al 2007).…”
Section: Introductionmentioning
confidence: 99%